2017
DOI: 10.1007/s00198-017-4037-9
|View full text |Cite
|
Sign up to set email alerts
|

Dietary acid load, trabecular bone integrity, and mineral density in an ageing population: the Rotterdam study

Abstract: SummaryWe studied the relation between a diet that is high in acid-forming nutrients (e.g. proteins) and low in base-forming nutrients (e.g. potassium) and bone structure. We showed a negative relation, which was more prominent if proteins were of animal rather than of vegetable origin and if intake of dietary fibre was high.IntroductionStudies on dietary acid load (DAL) and fractures have shown inconsistent results. Associations between DAL, bone mineral density (BMD) and trabecular bone integrity might play … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…In relation to specific nutrients, we established a plausible favorable relation between high vitamin A intake from the diet with fracture risk in overweight subjects [ 201 ]. We also determined that a diet high in acid-forming nutrients (e.g., proteins) may be detrimental to bone health in participants with high intake of dietary fibre [ 202 ]. Further, we identified dietary patterns influencing bone health, where beneficial effects on higher BMD were seen with “Health conscious” patterns in contrast to patterns characterized “Processed food” indicate potential susceptibility to presenting low BMD [ 117 ].…”
Section: Locomotor Diseasesmentioning
confidence: 99%
“…In relation to specific nutrients, we established a plausible favorable relation between high vitamin A intake from the diet with fracture risk in overweight subjects [ 201 ]. We also determined that a diet high in acid-forming nutrients (e.g., proteins) may be detrimental to bone health in participants with high intake of dietary fibre [ 202 ]. Further, we identified dietary patterns influencing bone health, where beneficial effects on higher BMD were seen with “Health conscious” patterns in contrast to patterns characterized “Processed food” indicate potential susceptibility to presenting low BMD [ 117 ].…”
Section: Locomotor Diseasesmentioning
confidence: 99%
“…As a consequence, the increased acid production can lead to a decrease in muscle mass [ 42 , 43 , 44 , 45 ]. In addition, regular acidic diet may trigger a reduction in bone mineralisation, an increase in urinary calcium excretion and pose a risk of bone fractures [ 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, there have been no studies on LD use and LS-TBS. TBS is a measurement related to bone microarchitecture which provides skeletal information that is not captured from the standard BMD measurements [31]. Also, TBS might be an appropriate measure to study in regard to lifestyle factors that are adaptable, such as dietary intake [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…TBS is a measurement related to bone microarchitecture which provides skeletal information that is not captured from the standard BMD measurements [31]. Also, TBS might be an appropriate measure to study in regard to lifestyle factors that are adaptable, such as dietary intake [31,32]. Other studies have reported lower TBS among individuals with primary hyperparathyroidism [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation